Beyond Drill And Practice: Innovative Strategies For Integrating Behaviorist Principles Into Arabic Vocabulary Learning - Hasanah, Amaliyatul; Insaniyah, Anyes Lathifatul (Instructional Development Journal, 2025)
This research investigates how Behaviorism could help high school students choose Arabic words.  This research will demonstrate how behaviorist teaching approaches affect word learning, therefore offering insightful analysis for theory and practical use.  The Arabic language is taught at MAN 3 Banyuwangi using behaviorism, this research looks at how. It uses a descriptive qualitative approach.  Data were gathered by observing, interviewing, and analyzing documents, and then examined using theme analysis.  Data validation was performed through triangulation, member checking, and peer debriefing to ensure the correctness and trustworthiness of the study results. The implementation of behaviorist learning methods at MAN 3 Banyuwangi has substantially improved the Arabic language and written skills of students, as evidenced by this research.  The drill method facilitates the retention of information through practice, while support enhances students' confidence and motivation. Using game tools like Kahoot and Quizizz helps people understand ideas quickly, makes lessons more engaging, and provides instant feedback, which improves the learning process. Combining technology with traditional methods improves education quality and makes learning more effective and enjoyable